Women's rights to land and communal forest tenure: A way forward for research and policy agenda in Latin America - Bose, P.; Larson, A.M.; Lastarria-Cornhiel, S.; Radel, C.; Schmink, M.; Schmook, B.; Vázquez García, V. (Elsevier, 2017)
In this synthesis paper, the authors of this Special Section contribute towards a collective research and policy agenda on rural and indigenous women's forest and land rights in Latin America. Based on the key lessons from the empirical evidence, we map out a way forward for the research agenda and suggest a few key institutional and policy priorities for rural Latin America.